The history of the Resistance taught in Italian schools by its key players. The commitment of the National Association of Italian Partisans (ANPI) in Tuscany - Oliviero, Stefano (Studi sulla Formazione/Open Journal of Education, 2016)
The history of the Italian Resistance to Nazi-Fascism is by its very nature vari-ously constructed and subject to political and cultural changes. Indeed, the historiography on the Resistance has benefitted from the contribution of specialists, common people, and even the contribution of witnesses who were key players in the struggle, i.e. the partisans. After joining together in ANPI in the aftermath of the Second World War, many partisans have produced a fair amount of memoirs, dedicating part of their time to defending and disseminating the value of their battle with the younger generations, including in schools. This contribution intends to weigh the educational and didactic commitment of ANPI, taking as a case study the region of Tuscany, one of the areas in which the partisan struggle was most intense. Founded in 1944 and still very active, one of ANPI’s goals has been to keep alive the profound significance of the opposition to Nazi-Fascism, disseminating the principles and values of this struggle. ANPI thus seeks to prevent that the history of the liberation movement can one day be forgotten or reduced to a few lines of text in history books. In partnership with historical institutes on the resistance and other veterans associations, ANPI has for a long time committed itself to teaching the history of the war of liberation in the nation’s schools, with their collaboration. This communication attempts to draw a framework for ex-partisans in the schools of Tuscany, in an effort to identify the themes and timeline of these activities, whether they have covered the Tuscan territory uniformly, and how they have been intertwined with the educational curriculum.